ANALISIS PENERAPAN TAX PLANNING DALAM UPAYA EFISIENSI BEBAN PAJAK PENGHASILAN (STUDI PADA PT. PASIFIK PETRA INDONESIA) - Herwanto, Theo Alfan; Tinangon, Jantje J.; Budiarso, Novi Swandari (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
Tax Planning is a legal effort that can be done by taxpayers. The action is legal because the tax prohibition is carried out in a way that does not violate the applicable law. Tax Planning is a means that supports to plan the excess used, so that it does not occur in paying taxes in accordance with Law no. 28 of 2007 article 1 paragraph 3 concerning General Provisions and Tax Procedures. This study aims to determine the implementation of Tax Planning, Tax Planning efficiency and effectiveness as well as accounting policies that affect the financial statements of PT. Pacific Petra Indonesia.The theory related to this research is the insurance theory where the state protects the safety of life, property, and the rights of its people. Therefore, people have to pay taxes in this research, namely income tax which is likened to an insurance premium because they get the protection guarantee.This study uses a qualitative descriptive approach because the research is based on data obtained through interviews and existing documents. The data used is primary data, where primary data consists of information obtained during the field trip, namely through interviews with informants, as well as data in the form of financial statements and annual tax returns and company permits. Informants in this study consisted of Administration and Finance Managers and their team who were directly involved in the preparation of financial and tax reports. The results of the study show that the application of Tax Planning with the use of Government Regulation Number 23 of 2018 is not appropriate, because Sales during 2020 exceed the specified gross income requirements. The tax that has been paid has not been effective and not efficient because the company should use the general corporate income tax rate of 25%. Regarding the research results, it is necessary to correct the 2020 Annual Income Tax Return. The accounting policies taken do not have much effect on the fiscal financial statements because the company chooses and implements policies in line with tax regulations.